The characteristics of intestinal microbiota in patients with type 2 diabetes and the correlation with the percentage of T-helper cells - Yang, Fan; Li, Jinyan; Wei, Longqin; Qin, Shenghua; Shi, Qingfeng; Lu, Siyan; Chu, Shuyuan (Frontiers in Microbiology, 2024)
Background Type 2 diabetes (T2D) is related to intestinal microflora changes and immune inflammation. We aimed to investigate the pattern of intestinal flora-systematic T helper (Th) cell linkage in T2D patients. Methods Participants with T2D diagnosed by physicians and healthy controls were enrolled in the study. The Th1, Th2, and Th17 cells from the peripheral blood were assessed by flow cytometry. The feces were collected. The V3–V4 variable region of 16S rRNA was sequenced and analyzed using bioinformatics. Principal coordinate analysis (PCoA) and non-metric multidimensional scaling (NMDS) analysis were performed to assess the beta diversity. The linear discriminant analysis (LDA) effect size (LEfSe) method was applied to identify amicrobial taxon specific to T2D. The Phylogenetic Investigation of Communities by Reconstruction of Unobserved States (PICRUSt) was conducted to identify the metabolic pathways. A network analysis was conducted by constructing a co-occurrence network. Results The percentages of the Th1 and Th17 cells in the peripheral blood were higher in patients with T2D than in controls. Among the top 30 genera of the intestinal microbiota, the levels of Lachnospiraceae_NK4A136_group, Ruminococcaceae_UCG002, and Eubacterium_hallii_group were lower in the patients with T2D than in controls. In the LEfSe analysis, it was observed that the Lachnospiraceae and Ruminococcaceae families were significantly different between patients with T2D and controls. Moreover, the Th1/Th2 ratio was positively correlated with the abundance of the Lachnoclostridium and Ruminococcus_torques_group genera. In the network analysis, the Th1/Th2 ratio, Ruminococcaceae_UCG-002, and Lachnospiraceae_NK4A136_group were the important nodes. Conclusion This study provided a preliminary picture of the crosstalk between the intestinal microbiome and systematic Th cells in patients with T2D. The findings of the study suggested that the network relationship among the intestinal microbiota, metabolites, and CD4+T lymphocyte immunity was unbalanced in the patients with T2D, which might have promoted the development of T2D. This presents a therapeutic opportunity to modulate gut immune reaction and then chronic inflammation by manipulating microbiome-specific Th-cell response.